PENGARUH TINGKAT RISIKO PADA PROSPEKTUS TERHADAP FENOMENA UNDERPRICING IPO DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Alya Ahshaina Refriazahra; Agus Purwanto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the impact of financial and non-financial risk factors on the phenomenon of underpricing in companies that conducted Initial Public Offerings (IPOs) in Indonesia during the period of 2020-2024. The financial variables examined include Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA) as a control variable, while the non-financial variables include Underwriter Reputation (PE) and Auditor Reputation (RA). The research employs multiple linear regression analysis to examine the relationship between these variables and the Initial Return (IR), which is used as an indicator of underpricing.The results indicate that Current Ratio (CR) has a significant positive effect on underpricing, with a p-value < 0.001. In contrast, Debt to Equity Ratio (DER), Underwriter Reputation (PE), and Auditor Reputation (RA) do not show a significant impact on underpricing, each with a p-value greater than 0.05. Return on Assets (ROA), used as a control variable, also shows a significant effect on underpricing. These findings suggest that company liquidity and profitability are more influential in affecting investor decisions on IPO pricing than external factors such as third-party reputations.This research contributes to the understanding of factors influencing underpricing in the Indonesian IPO market by showing that internal financial information of the company is more valued by investors, while auditor and underwriter reputations are less relevant. The implications of this study highlight the importance of company transparency and financial health in reducing underpricing and enhancing investor confidence.